Cover Image. Issue 11 (10th November 2019) - Mengistu, Girma; Shimelis, Hussein; Laing, Mark; Lule, Dagnachew
Abstract : The cover image, by Girma Mengistu et al., is based on the Original Article Assessment of sorghum genetic resources of Ethiopia for anthracnose (Colletotrichum sublineolum Henn.) resistance and agronomic traits . DOI: 10.1111/jph.12861 Cover image © Shimelis Hussein Images